Teaching practices in the construction of critical citizenship: experiences from Chile, Peru, and Costa Rica - Oyanedel Bernal, Carmen (2024)
This article provides a reflection on teaching experiences in the formation of citizenship, was prepared thanks to the participation in the Latin American Circle of Memories, Experiences and Teaching Dialogues, organized by Revista Perspectivas This space allowed nurturing the exchange of ideas on the opportunities offered by classrooms for the construction of critical citizenship. In this theoretical reflection, some social and environmental problems experienced in our countries are addressed, which function as a vehicle for students to think of themselves as collective actors integrated in a community; detailing some curricular contents and educational strategies that promote citizenship awareness. One of the main conclusions that emerged was the conceptualization of citizenship education as a form of school knowledge, whose purpose is to stimulate critical social thinking aimed at building democracy and social justice.